Nitrogen and inoculation with Rhizobium in different sources of Dalbergia nigra (Vellozo) - Carlos, Leandro; Venturin, Nelson; Lopes, Ranielle Santos; Costa, Andréia Mendes da; Venturin, Regis Pereira (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
The jacarandá-da-Bahia (Dalbergia nigra) presents high potential for sustainable forest management, as well as producing an excellent wood used in the manufacture of furniture and musical instruments. The objective of this study was to evaluate the effects between nitrogen doses and inoculation with Rhizobium in D. nigra procenances, in greenhouse conditions and low fertility Oxisoil. The experimental design consisted of 5 nitrogen doses (0, 50, 100, 200 and 400 mg/kg of N), with and without Rhizobium specific for jacaranda (BR 8404 - 3 localities, Lavras, MG, Rio Doce, MG, and Santa Tereza, ES). The morphological characteristics analyzed were: biometrics, biomass and quality of D. nigra. Fertilization with 217.5 mg/kg of nitrogen influenced all morphological characteristics, being the Rio Doce provenance the best response to N doses. Rhizobium inoculation was shown to be more effective at lower doses of nitrogen fertilization. Thus, it was possible to verify that the D. nigra provenance, Rio Doce and Santa Teresa, respond to nitrogen fertilization and that for the same the inoculation presented positive results.